Development of Android-Based Mobile Learning Media on Market Balance Chapter Class X SMA Negeri 12 Surabaya - Aulya Sandy; Retno Mustika Dewi (Universitas Muhammadiyah Enrekang, 2024)
This development research was carried out based on the lack of understanding of students and learning media in economics subjects. The aim of this research was to increase students' understanding through mobile learning media. This research uses the ADDIE model. The subjects of this research were students in class X7 of SMA Negeri 12 Surabaya. The design used is One Group Pretest Posttest. The research results showed that material expert validation obtained a percentage of 87%, including in the